Discourse Analysis in E-Learning-Based Course Using Moodle Platform: An Experimental Design - Putri, Silvia Eka; Hamuddin, Budianto; Nursafira, Mutia Sari; Derin, Tatum (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2020)
The COVID-19 pandemic has caused educational institutions all over the world to migrate their teachings online. Since Indonesian government issued the SK Mendiknas No. 107/U/2001, educational institutions had to steadily integrate their learning process with technology. So, this study intends to investigate the effectiveness of using the open-source learning platforms known as Moodle in a selected university, Universitas Lancang Kuning (Unilak) in Indonesia. While multiple courses uses Moodle, this study selected to analyse the 2017/2018 fifth semester students as they are the ones who pioneered Moodle for other classes to use. With a quasi-experimental research design, this study used four types of test to calculate the results of the essay pre-test and post-test on both experimental and control classes. With the eventual mean of 65.53 for the experimental class and 63.25 for the control, this study proved that Moodle does effectively improve Indonesian university EFL students’ learning compared to conventional lecture-style learning. Future research is hoped to extend or compare this study with an investigation on how university EFL students are using e-learning during the COVID-19 pandemic and other factors that have not been covered in this empirical study.